Southey’s “New System”: the monitorial controversy and the making of the “entire man of letters” - Duggett, Tom (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
This essay reads Southey’s repeated writings between 1806 and 1812 on the "monitorial method" of education, and the religious-political controversy over its invention and application. I suggest that this repetitive writing provides insights into Southey's career, as well as wider issues of Romantic historicism, originality, authorial integrity, and system. The first section considers Southey’s associative style, and his connection between the use of humiliating punishments in Joseph Lancaster’s monitorial schools and the threat of domestic revolution. The second section reads Southey’s support for Lancaster's rival Andrew Bell as part of his search for a systematic basis for the pro-war and anti-Catholic terms of his conservatism, in the context of the periodical culture-wars between the Quarterly and the Edinburgh Review. Section three then explores Southey’s changing position in the Bell-Lancaster controversy in the light of his “art of historical book-keeping,” and suggests a contorted literary consistency behind the alleged political “apostasy.” The coda reflects on the contrast of system and style between Southey and Coleridge, and their diverging visions of education and the "national church.”